2022
DOI: 10.1186/s12992-022-00830-8
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and newborn health for the urban poor: the need for a new mental model and implementation strategies to accelerate progress

Abstract: BackgroundUrbanization challenges the assumptions that have traditionally influenced maternal and newborn health (MNH) programs. This landscaping outlines how current mental models for MNH programs have fallen short for urban slum populations and identifies implications for the global community. We employed a three-pronged approach, including a literature review, key informant interviews with global- and national-level experts, and a case study in Bangladesh.Main bodyOur findings highlight that the current men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 56 publications
(56 reference statements)
0
7
0
Order By: Relevance
“…The analysis of 22 large African cities also showed variable levels of essential care elements (>99% of babies born in health facilities were weighed but only half of babies initiated breast feeding within an hour of birth) and high levels of early discharge from health facilities following both vaginal and caesarean section births in Dar es Salaam. Further, literature shows that poor women, especially those living in informal settlements, might also receive poorer quality of care, encounter stigmatising attitudes and disrespectful care in health facilities 31–33. Our additional analysis on the timing of deaths showed that a comparatively low percentage of neonatal deaths in core urban areas occurred on the day of birth compared with semi-urban and rural areas.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The analysis of 22 large African cities also showed variable levels of essential care elements (>99% of babies born in health facilities were weighed but only half of babies initiated breast feeding within an hour of birth) and high levels of early discharge from health facilities following both vaginal and caesarean section births in Dar es Salaam. Further, literature shows that poor women, especially those living in informal settlements, might also receive poorer quality of care, encounter stigmatising attitudes and disrespectful care in health facilities 31–33. Our additional analysis on the timing of deaths showed that a comparatively low percentage of neonatal deaths in core urban areas occurred on the day of birth compared with semi-urban and rural areas.…”
Section: Discussionmentioning
confidence: 71%
“…Further, literature shows that poor women, especially those living in informal settlements, might also receive poorer quality of care, encounter stigmatising attitudes and disrespectful care in health facilities. [31][32][33] Our additional analysis on the timing of deaths showed that a comparatively low percentage of neonatal deaths in core urban areas occurred on the day of birth compared with semi-urban and rural areas. Interpretation is difficult, but one explanation may be better access to emergency obstetrical care including neonatal resuscitation in core urban compared with rural areas.…”
Section: Bmj Global Healthmentioning
confidence: 87%
“…A systematic review pooled 22 studies and found that around 57% of the neonatal deaths occurred during the first 3 days of life, as neonatal mortality due to asphyxia, prematurity, and malformations were mostly caused during these first 3 days of life [ 46 ]. These high rates, along with our study, demonstrate the lack of evidence-based interventions beginning in the antenatal period, which is relatively low among urban slum mothers [ 46 48 ]. Relatively lower mortality for caesarean delivery than vaginal on the 1st day of life could be due to the care received by the mother and newborn from the hospital, as the caesarean-delivered mother had to stay for a longer time at the hospital [ 2 , 49 52 ].…”
Section: Discussionmentioning
confidence: 61%
“…Moreover, with the global expansion of towns and cities, there has for some time been a trend of urbanization of poverty [4]. The convenience of living in cities (shorter distances, accessibility of services, social networks) benefits a small percentage of population with millions of urban-dwellers being excluded [3]; which in turn has implications for maternal [5] and child health [6]. A study drawing from Demographic and Health Surveys in Least Developed Countries showed significant inequalities in children's nutritional outcomes, with higher inequalities in the most rapidly urbanizing countries [7].…”
Section: Introductionmentioning
confidence: 99%
“…A study of 22 African cities showed disruptions in the maternal continuum of care, characterized drop offs in antenatal care, childbirth and postpartum care, with varying reliance on public and private sector use, and use of hospitals across cities [8]. Another study, drawing on data from seven cities in LMICs highlighted issues relating to availability, accessibility, quality of MCH services as well as delayed care-seeking [5]. In a study on 30 developing countries, it was noted that the urban poor did not have better access to maternal healthcare despite proximity to healthcare services [9].…”
Section: Introductionmentioning
confidence: 99%